Astrocyte-shed extracellular vesicles regulate the peripheral leukocyte response to inflammatory brain lesions - Dickens, A; Tovar-y-Romo, L; Yoo, S; Trout, A; Bae, M; Kanmogne, M; Megra, B; Williams, D; Witwer, K; Gacias, M; Tabatadze, N; Cole, R; et al. (American Association for the Advancement of Science, 2017)
Brain injury induces a peripheral acute cytokine response that directs the transmigration of leukocytes into the brain. Because this brain-to-peripheral immune communication affects patient recovery, understanding its regulation is important. Using a mouse model of inflammatory brain injury, we set out to find a soluble mediator for this phenomenon. We found that extracellular vesicles (EVs) shed from astrocytes in response to intracerebral injection of interleukin-1β (IL-1β) rapidly entered into peripheral circulation and promoted the transmigration of leukocytes through modulation of the peripheral acute cytokine response. Bioinformatic analysis of the protein and microRNA cargo of EVs identified peroxisome proliferator–activated receptor α (PPARα) as a primary molecular target of astrocyte-shed EVs. We confirmed in mice that astrocytic EVs promoted the transmigration of leukocytes into the brain by inhibiting PPARα, resulting in the increase of nuclear factor κB (NF-κB) activity that triggered the production of cytokines in liver. These findings expand our understanding of the mechanisms regulating communication between the brain and peripheral immune system and identify astrocytic EVs as a molecular regulator of the immunological response to inflammatory brain damage.